Action v inaction: a case history in ethics. Issue 4 (20th August 2003) - Berry, P
Abstract : The motives behind the author's decision to resuscitate a patient are examined. This is prompted by the realisation that he ignored the man's apparent wish not to be saved for fear of criticism from both relatives and colleagues. The way in which decisions are made when the interests of the doctor and the patient clash are briefly explored. Self interest may play a more significant role than is commonly accepted.